Identification of somatic mutations in postmortem human brains by whole genome sequencing and their implications for psychiatric disorders. Issue 4 (10th February 2018) - Nishioka, Masaki; Bundo, Miki; Ueda, Junko; Katsuoka, Fumiki; Sato, Yukuto; Kuroki, Yoko; Ishii, Takao; Ukai, Wataru; Murayama, Shigeo; Hashimoto, Eri; Nagasaki, Masao; Yasuda, Jun; et al.
Abstract : Aim: Somatic mutations in the human brain are hypothesized to contribute to the functional diversity of brain cells as well as the pathophysiology of neuropsychiatric diseases. However, there are still few reports on somatic mutations in non‐neoplastic human brain tissues. This study attempted to unveil the landscape of somatic mutations in the human brain. Methods: We explored the landscape of somatic mutations in human brain tissues derived from three individuals with no neuropsychiatric diseases by whole‐genome deep sequencing at a depth of around 100. The candidate mutations underwent multi‐layered filtering, and were validated by ultra‐deep target amplicon sequencing at a depth of around 200 000. Results: Thirty‐one somatic mutations were identified in the human brain, demonstrating the utility of whole‐genome sequencing of bulk brain tissue. The mutations were enriched in neuron‐expressed genes, and two‐thirds of the identified somatic single nucleotide variants in the brain tissues were cytosine‐to‐thymine transitions, half of which were in CpG dinucleotides. Conclusion: Our developed filtering and validation approaches will be useful to identify somatic mutations in the human brain. The vulnerability of neuron‐expressed genes to mutational events suggests their potential relevance to neuropsychiatric diseases.